2013
DOI: 10.4161/derm.24156
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of the vitamin D endocrine system (VDES) for tumorigenesis, prevention, and treatment of non-melanoma skin cancer (NMSC)

Abstract: Solar UV (UV)-B-radiation exerts both beneficial and adverse effects on human health. On the one hand, it is the most important environmental risk factor for the development of non-melanoma skin cancer [NMSC; most importantly basal (BCC) and squamous (SCC) cell carcinomas], that represent the most common malignancies in Caucasian populations. On the other hand, the human body’s requirements of vitamin D are mainly achieved by UV-B-induced cutaneous photosynthesis. This dilemma represents a serious problem in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 121 publications
(326 reference statements)
1
15
0
2
Order By: Relevance
“…Many investigations have indicated that vitamin D 3 action reduces risk of nonmelanoma skin cancers, maybe modulating p53 response to DNA damage in SCC 17,18. The association between plasma 25-hydroxy-vitamin D (25(OH)D) levels and the incident risk of SCC has been recognized, and could be, together with photoprotection, one of the parameters based on which patients having major risk factors for the development of SCC can be treated.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigations have indicated that vitamin D 3 action reduces risk of nonmelanoma skin cancers, maybe modulating p53 response to DNA damage in SCC 17,18. The association between plasma 25-hydroxy-vitamin D (25(OH)D) levels and the incident risk of SCC has been recognized, and could be, together with photoprotection, one of the parameters based on which patients having major risk factors for the development of SCC can be treated.…”
Section: Discussionmentioning
confidence: 99%
“…Upon binding of Shh protein or a mutation in the SSD of Ptch, the pump is turned off, which allows oxysterols to accumulate around Smo. This accumulation of sterols renders Smo to become active or stay on the membrane for a longer period of time (Reichrath and Reichrath, 2013). In contrast to Drosophila , vertebrates possess another level of hedgehog regulation through ligand-dependent antagonism mediated by Hh-interacting protein 1 (Hhip1).…”
Section: Sonic Hedgehog Signaling: Components Routes and Mechanismmentioning
confidence: 99%
“…Vitamin D levels have been reported to be associated with incidence and outcomes of certain types of cancer, including NMSC . In addition, some studies have shown relationships between VDR gene polymorphisms and the risk of BCC .…”
mentioning
confidence: 99%
“…In addition, some studies have shown relationships between VDR gene polymorphisms and the risk of BCC . In addition, vitamin D‐binding protein (VDBP) single‐nucleotide polymorphisms (SNPs) affect 25(OH)D levels, thereby influencing skin carcinogenesis . Recently, genetic variations within VDR binding sites have emerged as important contributors to transcription factor affinity, and therefore, their impact on the function of VDES has begun to be considered .…”
mentioning
confidence: 99%